Influence of volume and surface strengthening on the scale deformation levels of low-alloyed steel; Korus 2001; Vol. 1 - Panin V. E. Viktor Evgenyevich; Slosman A. I.; Antipina R. A.; Ovechkin B. B. Boris Borisovich; Litvinenko A. V. (2001, 2001)
Plastic deformation, in common case, proceeds the mutual co-ordination on different scale levels. The tension concentrators and possibility of spreading the lines of localized deformation of corresponding scale level for deformation realization on this level. Both of them are determined by a great number of factors. In this work the influence of structure dimensions the surface state on deformation localization on 12×1M steel mesoscale level was investigated. The dimensions of inside structure were varied by thermal processing condition and the surface state was varied by processing in nitrogen containing glow discharge plasma. It was shown that by increasing the small-grain samples plastic deformation takes place by spreading localized deformation mesobands from the initial mesoconcentrators. By stretching it takes place by Luders' line shifting. By compressing it takes place by forming the mesolines system of localized deformation in the connected directions of maximum tangential stress. In both cases insignificant volume of materials is involved.